Dinner and a Conversation: Transgender Integration at West Point and Beyond - Morten G. Ender; Diane M. Ryan; Danielle A. Nuszkowski; Emma Sarah Spell; Charles B. Atkins (Social Sciences, 2017)
In 2016, the United States military lifted the ban on transgender members serving and are expected to begin accessions of transgender service members in 2017. A paucity of research exists on transgender matters in the military, especially on attitudes towards cisgender service members. This study deploys a qualitative methodology, comprised of 21 focus groups of undergraduate cadets and advanced schooled Army officers (N = 110), at the United States Military Academy at West Point, New York, using a semi-structured interview protocol. Overall, a diversity of experiences and familiarity with transgender people surfaced among cadets and officers. We distinguish between experiences and familiarity on a spectrum by introducing notions of transgender tourism and cosmopolitanism. Major concerns associated with (un)comfortableness emerged from the focus groups including privacy, physical standards, well-being, and costs. Interventions are offered by the participants based on their major concerns. We recommend education, increased cosmopolitism, privacy considerations, narrowing the civil-military propinquity gap, and more studies of diversity and inclusion issues in the military.